2021
DOI: 10.1177/0022243721991100
|View full text |Cite
|
Sign up to set email alerts
|

Testing Theories of Goal Progress in Online Learning

Abstract: Online educational platforms increasingly allow learners to consume content at their own pace with on-demand formats, in contrast to the synchronous content of traditional education. Thus, it is important to understand and model learner engagement within these environments. Using data from four business courses hosted on Coursera, we model learner behavior as a two-stage decision process, with the first stage determining across-day continuation versus quitting and the second stage determining within-day choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…The content of this special issue also examines many different actors including students (Narang, Yadav, and Rindfleisch 2022), salespeople (Singh, Sen, and Borle 2022), curriculum development departments (Sen and Tucker 2022), grocery shoppers (Bollinger et al 2022), school administrators (Dolbec et al 2022), home tutors (Kim et al 2022), and buyers of educational products and services (Tu, Kwon, and Gao 2022). Consistent with our definition, this special issues touches on pedagogical content (Krishna and Orhun 2022;Sen and Tucker 2022), the process of gaining and imparting knowledge (Lu, Bradlow, and Hutchinson 2022;Narang, Yadav, and Rindfleisch 2022), and educational outcomes (Bollinger et al 2022;Goli, Chintagunta, and Sriram 2022;Singh, Sen, and Borle 2022).…”
Section: Education: Definition and Scopementioning
confidence: 87%
See 2 more Smart Citations
“…The content of this special issue also examines many different actors including students (Narang, Yadav, and Rindfleisch 2022), salespeople (Singh, Sen, and Borle 2022), curriculum development departments (Sen and Tucker 2022), grocery shoppers (Bollinger et al 2022), school administrators (Dolbec et al 2022), home tutors (Kim et al 2022), and buyers of educational products and services (Tu, Kwon, and Gao 2022). Consistent with our definition, this special issues touches on pedagogical content (Krishna and Orhun 2022;Sen and Tucker 2022), the process of gaining and imparting knowledge (Lu, Bradlow, and Hutchinson 2022;Narang, Yadav, and Rindfleisch 2022), and educational outcomes (Bollinger et al 2022;Goli, Chintagunta, and Sriram 2022;Singh, Sen, and Borle 2022).…”
Section: Education: Definition and Scopementioning
confidence: 87%
“…This inclusive and expansive definition and scope of education is reflected in the content of this special issue, Although we discuss individual articles in detail subsequently, we draw attention to the fact that the content of this special issue spans a wide variety of educational avenues including K-12 education (Sen and Tucker 2022;Zhou, Gill, and Liu 2022), university education (Krishna and Orhun 2022), online education (Lu, Bradlow, and Hutchinson 2022;Narang, Yadav, and Rindfleisch 2022), and sales training (Singh, Sen, and Borle 2022). The content of this special issue also examines many different actors including students (Narang, Yadav, and Rindfleisch 2022), salespeople (Singh, Sen, and Borle 2022), curriculum development departments (Sen and Tucker 2022), grocery shoppers (Bollinger et al 2022), school administrators (Dolbec et al 2022), home tutors (Kim et al 2022), and buyers of educational products and services (Tu, Kwon, and Gao 2022).…”
Section: Education: Definition and Scopementioning
confidence: 99%
See 1 more Smart Citation
“…Once learners access online material, they may extend their learning sessions because it is easier and more convenient than accessing the material later. Researchers have found that students prefer massed presentations of information (Son & Simon, 2012), and others propose that bingeing can benefit online learning because, somewhat similar to television viewing, consumers derive enjoyment by experiencing a fluency and flow to their learning (Lu et al, 2018). However, consumers are not good predictors of their learning (Vesonder & Voss, 1985), so highlighting the flexibility of online education may inadvertently facilitate binge learning, which could lead to poor study outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within the context of binge-watching, early bingeing is common, and releasing program material all at once can increase binge behavior (D’Souza, 2020). In the educational context, some research suggests that releasing material at the beginning of the semester can lead to Front-bingeing behavior (Lu et al, 2018). Large MOOCs require posting all material at the start of class to accommodate all students, but this is also standard practice in many online programs that tout flexibility in learning, such as the online classroom which is the context of our studies.…”
Section: Literature Reviewmentioning
confidence: 99%